2014
DOI: 10.1126/science.1239947
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis Reveals the Origin and Therapy-Driven Evolution of Recurrent Glioma

Abstract: Tumor recurrence is a leading cause of cancer mortality. Therapies for recurrent disease may fail, at least in part, because the genomic alterations driving the growth of recurrences are distinct from those in the initial tumor. To explore this hypothesis, we sequenced the exomes of 23 initial low-grade gliomas and recurrent tumors resected from the same patients. In 43% of cases, at least half of the mutations in the initial tumor were undetected at recurrence, including driver mutations in TP53, ATRX, SMARCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

62
1,063
10
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,187 publications
(1,172 citation statements)
references
References 56 publications
62
1,063
10
14
Order By: Relevance
“…Exome sequencing of recurrent tumors revealed alterations in both the mTOR (MTOR, AKT, PTEN a.o.) and RB (RB, CDK4,6, CDKN2A) pathway (Johnson et al 2014). Similar events might be ongoing in NET, with potential impact on sequencing of therapies and support re-biopsy as a valuable tool for directing treatment.…”
Section: Impact Of Genomic Profiling On Therapymentioning
confidence: 99%
“…Exome sequencing of recurrent tumors revealed alterations in both the mTOR (MTOR, AKT, PTEN a.o.) and RB (RB, CDK4,6, CDKN2A) pathway (Johnson et al 2014). Similar events might be ongoing in NET, with potential impact on sequencing of therapies and support re-biopsy as a valuable tool for directing treatment.…”
Section: Impact Of Genomic Profiling On Therapymentioning
confidence: 99%
“…A recent study identified a distinct mutation profile of recurrent glioma that varied from the initial mutation analyses in the same patient (24). The exomes of 23 initially low-grade gliomas and recurrent tumors resected from the same patients were sequenced and the mutation profiles were mutually compared.…”
Section: Perspectives On Novel Therapies For Gbmmentioning
confidence: 99%
“…Glioma is a major therapeutic challenge due to numerous factors, including the tendency to adapt resistance against antiangiogenic agents, and intratumoural cellular heterogeneity that varies over the course of the disease and its treatment (3). To improve the poor prognosis for patients with glioma, it is important to understand the molecular mechanisms underlying and supporting tumor cell survival and invasion.…”
Section: Introductionmentioning
confidence: 99%